Court of Justice of the European Union and the autonomous restrictive measures against natural and legal persons and non – state entities within the Common Foreign and Security Policy - Tučić, Boris (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
As a part of its specific policies, the EU creates and implements numerous restrictive measures against different subjects. In recent years, the most interesting ones, especially from the perspective of the Court of Justice of the European Union (CJEU), have been the autonomous restrictive measures against natural and legal persons and other non-state entities within the Union`s Common Foreign and Security Policy (CFSP). After years of legal wandering in this regard, the Lisbon Treaty finally offered an explicit legal basis for this kind of measures, envisaging, as well, for the first time, the CJEU`s jurisdiction in the field of CFSP in some cases, including the one related to reviewing the legality of decisions providing for restrictive measures against natural or legal persons adopted by the Council of the EU on the basis of Chapter 2 of the Title V of the Treaty of the European Union.In this regard, subject of this paper are the activities of the EU courts related to the autonomous restrictive measures against individual subjects, analyzed at several relevant, although inseparable levels. First one considers the intention of the CJEU to “use” the situation regarding the autonomous restrictive measures in order to strengthen its position and competences within the CFSP. The second one is oriented to the efforts of the courts to secure the balance between the effectiveness of the CFSP instruments, on the one side, and the protection of some of the major principles and values of the EU legal order, on the other, such as the rule of law, legal certainty, effective judicial protection or the protection of human rights as its guaranteed by the EU Law in general. Thirdly, very important step in this context has been the jurisprudential identification of the key procedural requirements that Council`s decisions providing for restrictive measures must fulfill as well (aka the designation criteria, statements of reasons criteria and supporting evidence criteria). By constantly insisting on the fulfillment of these criteria, the EU courts made a pressure on the Council to improve its decisions providing restrictive measures in qualitative manner.Recent jurisprudence, such as the Rosneft or Bank Refah Kargaran cases, shows that there is still enough space for the Court`s interventions in this field and that some interesting court`s decisions, related to its position within the CFSP or the general relation between the CFSP and other forms of Union`s external activities, could be expected in years to come.
Keywords: Common Foreign and Security Policy; autonomous restrictive measures; jurisprudence; natural and legal persons and other non-state entities; CJEU; General Court; procedural criteria; human rights